Superelasticity and force plateau of nickel-titanium springs: an in vitro study - Vieira,Camila Ivini Viana (2016)
abstract Objective: This paper analyzed whether nickel-titanium closed coil springs (NTCCS) have a different superelastic (SE) behavior according to activation and whether their force plateau corresponds to that informed by the manufacturer. Methods: A total of 160 springs were divided into 16 subgroups according to their features and activated proportionally to the length of the extensible part (NiTi) of the spring (Y). The force values measured were analyzed to determine SE rates and force plateaus, which were mathematically calculated. These plateaus were compared to those informed by the manufacturer. Analysis of variance was accomplished followed by Tukey post-hoc test to detect and analyze differences between groups. Results: All subgroups were SE at the activation of 400% of Y length, except for: subgroups 4B and 3A, which were SE at 300%; subgroups 4E and 4G, which were SE at 500%; and subgroup 3C, which was SE at 600%. Subgroup 3B did not show a SE behavior. Force plateaus depended on activation and, in some subgroups and some activations, were similar to the force informed. Conclusions: Most of the springs showed SE behavior at 400% of activation. Force plateaus are difficult to compare due to lack of information provided by manufacturers.